Verejné výdavky a sociálny štát v čase hospodárskej krízy - Zubaľová, Alena; Vassová, Adriana (Univerzita Pardubice, 2010)
The welfare state has several objectives, implementation of which brings increasing pressure on public expenditure. Social policy is part of economic policy among its key elements include: social support, social assistance, employment, housing and others. The public sector plays an important role in achieving social policy objectives. In a time of economic crisis, the question arises whether to support growth, or rather a reduction in public expenditure in relation to the building of the welfare state.
Keywords: public expenditure; public sector; welfare state; social policy; economic crisis